Female students’ responses to change - Pilotti, Maura A. E.; Faisal, Nouf Y.; Hassan, Samia A. M.; Cavazos, Sandra E.; Elmoussa, Omar (Frontiers in Education, 2022)
The present research examined students’ responses to the post-pandemic instructional world. The participants were women of a society in transition from a patriarchal order to one fostering gender equity in education and employment. At the end of the first semester that highlighted their return to campus, students completed a questionnaire on their self-efficacy and a questionnaire on their responses to the post-pandemic learning environment as compared to the pandemic one. Three patterns of responses to change emerged, involving how students managed motivation, effort, and time, self-regulated attention, and invested time and effort: adaptation, maintenance, and surrender. Responses varied with self-efficacy. These multidimensional patterns were interpreted as informing the development of a tailored approach for support services in the post-pandemic ecosystem.